Pengaruh Digital Payment, Religiositas, dan Literasi Zakat terhadap Keputusan Membayar Zakat dengan Kualitas Layanan sebagai Intervening - Slamet Budi Hariyanto; Agus Eko Sujianto; Binti Nur Asiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is based on the fact that digital zakat payments are increasingly popular with the wider community. This is evidenced by the increasing number of digital zakat payments from year to year, so that digital zakat payments contribute to increasing zakat payments. This study uses a quantitative approach. The type of data used is primary data using questionnaires. In this study, the sample used was a total of 98 muzakki at the Amil Zakat Institute in Tulungagung Regency, but for reasons of suitability for filling out a complete questionnaire filled out a questionnaire of 80 respondents, so in this study the sample was taken by 80 respondents. The data analysis technique used is Multiple Linear Regression Analysis using SPSS. The results of his research show that there is a significant influence between digital payments on people's decisions in paying zakat at the Amil Zakat Institution of Tulungagung Regency; There is a significant influence between religiosity on people's decisions in paying zakat at the Amil Zakat Institution of Tulungagung Regency; There is a significant influence between zakat literacy on people's decisions to pay zakat at the Amil Zakat Institution of Tulungagung Regency; service quality can mediate between digital payments and community decisions; the quality of service can mediate between religiosity and community decisions; service quality cannot mediate between zakat literacy and community decisions; The quality of services of the Amil Zakat Institute in Tulungagung Regency affects the community's decision to pay zakat at the Amil Zakat Institute of Tulungagung Regency.